Aromatum, et simplicium aliquot medicamentorum apud Indos nascentium historia, 1567. Étant la traduction latine des Coloquios dos simples e drogas e cousas medicinais da India de Garcia da Orta : Facsimile - Orta, Garcia da, (Dutch Classics on History of Science ;, 1963)
Original printed in Portuguese in Goa, Ionnes de Endum, 1564. This facsimile is a reprint of the edition Antverpiae, ex officina Christophori Plantini, 1567.